Optimalisasi Usaha Mikro Kecil di Desa Kassi Melalui Ekonomi Kreatif - Nurman Nurman; Chalid Imran Musa; Anwar Anwar; Zainal Ruma; Muhammad Ilham Wardhana Haeruddin (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community empowerment activity was carried out in Kassi Village, Rumbia District, Jeneponto Regency. Kassi Village is located in a highland area and has agricultural and plantation land that includes secondary crops and horticulture. Kassi Village also has attractive tourism potential and an art studio that showcases various traditional dances. This wealth of resources supports the growth of Micro and Small Enterprises (MSEs) in Kassi Village, with 89 MSEs recorded in 2022. However, this abundance of natural potential has not yet contributed significantly to the MSEs, which tend to remain stagnant. To address this issue, the Tim PKM provided optimization services for Micro and Small Enterprises (MSEs) through a business workshop program. The method used in this community empowerment effort is a capacity building method with a participatory approach. The results of this activity showed that the problems faced by business actors were effectively resolved through intensive training and the formation of the Baji Kassi Community to optimize the performance of MSEs in Kassi Village by providing consultation services.